MANAGEMENT STRATEGY FORNPUBLICATION OF LASALLE COLLEGE INDONESIA’S ACHIEVEMENTS THROUGH FACEBOOK SOCIAL MEDIA - Yosika Yosika (Universitas Mercu Buana, 2022)
The use of social media Facebook as an alternative to new media in online publication activities to be able to reach a wider and targeted audience. As a result, there are more followers on LaSalle College Indonesia social media than other similar educational institutions. This research was conducted to find out how the management strategy of publications conducted by Lasalle College Indonesia through Facebook social media using the stages of managing publications from Manager Creations Publications